The Mediterranean diet: A short review of the health benefits - A. Revelas; D. Arvanitakis (South African Family Practice)
There is an urgent need to preserve the traditional diet in the Mediterranean countries and to stress its important contribution to the public health. The traditional Mediterranean diet can be revitalised within a modern environment and lifestyle and be adopted not only by inhabitants of the Mediterranean region, but also by people in other countries as a health-promoting model. The Mediterranean diet can significantly decrease the risk of overall mortality.